Pengaruh Kedisplinan dan Lingkungan Kerja Terhadap Kinerja Pegawai di Lembaga Perlindungan Saksi dan Korban Jakarta - Rama Ferdiansyah; Mahmud Syarif; Desy Tri Anggarini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of discipline and work environment on employee performance at the Witness and Victim Protection Agency (LPSK) Jakarta. Enhancing employee performance is crucial for organizational success, and discipline and work environment factors are often identified as important predictors. The research employed a quantitative method with a survey approach, where data was collected through questionnaires distributed to employees of LPSK Jakarta. The research sample was selected using purposive sampling. The collected data were analyzed using multiple linear regression to test the proposed hypotheses. The results of this study are expected to show that discipline and work environment, both partially and simultaneously, have a significant influence on employee performance. The practical implications of this research are to provide recommendations to LPSK Jakarta for developing policies and programs that can enhance discipline and create a conducive work environment to optimize employee performance.